New Data on Ectoparasites of the Caucasian Squirrel Sciurus anomalus (Rodentia: Sciuridae) in Türkiye: A Case Report - Gökhan Eren (Türkiye Parazitoloji Dergisi)
Sciurus anomalus Güldenstädt, 1785, known as the Caucasian squirrel, is a rodent distributed in all geographical regions of Türkiye. The material of this study consists of ectoparasites collected from male S. anomalus found dead on the highway (Karasu, Sakarya, Türkiye). As a result of microscopic examination, the specimens were identified: ticks as Ixodes ricinus Linnaeus, 1758 (larvae and nymph), sucking louses as Neohaematopinus syriacus Ferris, 1923 (female), and fleas as Monopsyllus sciurorum sciurorum (Schrank, 1803) (female and male). In this study, the presence of Ixodes ricinus infestation on Sciurus anomalus is reported for the first time in Türkiye.